An Analysis of the Impact of TikTok Content on the Behavior of Children Aged 5–6 Years at TK IT Baitusshalihin Banda Aceh - Cut Syarah; Fitriah Hayati; Raudha Meutia (Lembaga Penelitian dan Pendidikan Mandala, 2026)
The rapid development of digital technology has influenced various aspects of life, including the behavior of early childhood children. One of the social media platforms widely used today is TikTok, which provides a variety of engaging audio-visual content that is easily accessible to different age groups, including children. This study aims to analyze the impact of TikTok content on the social and emotional behavior of children aged 5–6 years at TK IT Baitusshalihin Banda Aceh and to examine the role of teachers and parents in supervising children's use of digital media. This study employed a descriptive qualitative approach involving 8 children aged 5–6 years, 2 classroom teachers, and 3 parents as research participants. Data were collected through observation, interviews, and documentation. The data obtained were analyzed using the Miles and Huberman model, which includes data reduction, data display, and conclusion drawing. The results of the study indicate that most children are familiar with TikTok content and tend to imitate various videos they watch, such as songs, dance movements, facial expressions, and speaking styles. TikTok content has an impact on children's social behavior, particularly in the way they interact and communicate with their peers. In addition, TikTok content also influences children's emotional behavior through changes in how they express themselves and respond to certain situations. The effects are not always negative. TikTok can enhance children's creativity, confidence in self-expression, and social interaction when used appropriately. However, excessive use without proper supervision may lead children to imitate behaviors that are not suitable for their age and developmental stage. Therefore, the roles of teachers and parents are crucial in providing supervision, guidance, and the selection of appropriate content so that the use of digital media can optimally support children's social and emotional development